Economic Valuation of Traditional Mining Crude Oil in Wonocolo Village - Suryanto, Suryanto; Gusti Pramono, Maulidika (JEJAK, 2024)
This research aims to identify the mining activities of crude oil resources in Wonocolo Village. The government will identify the benefits and impacts of already-known activities will be identified from this activity. Economic valuation analysis calculates These benefits and impacts in monetary terms. The aim is to find out the monetary value of benefits and impact so that they can be used to develop a related policy. The primary and secondary data are collected through interviews and observation. The sampling method uses purposive sampling, and the research method is quantitative descriptive using analysis techniques in the form of economic valuation. The results of this study indicate that the economic valuation of the traditional mining activities of crude oil resources in Wonocolo Village has a positive Rp value. 33.214.795.622,-/year. This positive value is because the value of benefits is greater than the impacts they are Rp. 33.478.992.562,-/year and Rp. 273.196.940,./year.